Synthesis, Structure, and Magnetic Study of Two Tridecanuclear Planar Cobalt Clusters with Unique Core Geometries. Issue 32 (19th September 2013) - Peng, Yan; Tian, Chong‐Bin; Lan, Yan‐Hua; Magnani, Nicola; Li, Qi‐Peng; Zhang, Hua‐Bin; Powell, Annie K.; Du, Shao‐Wu
Abstract: The reaction of Co(NO3 )2 · 6H2 O with N, N ‐diethanolamine (H2 L1 ) in the presence of sodium acetate, using triethylamine as a base, leads to a tridecanuclear mixed‐valent cobalt cluster [Co II 9 Co III 4 (OH)6 (H2 O)2 (L1 )8 (OAc)4 ](NO3 )4 · 24H2 O (1 ). Similar reaction with a newly designed hydroxy‐ and nitrogen‐rich chelating ligand 2‐[bis(pyridin‐2‐ylmethyl)amino]‐2‐(hydroxymethyl)propane‐1, 3‐diol (H2 L2 ) gives a mixed‐valent Co13 cluster [Co II 7 Co III 6 (OH)12 (L2 )6 ](NO3 )8 · 10H2 O (2 ). The cobalt ions in both1 and2 are nearly coplanar, forming a novel shieldlike configuration for1 and a unique hexagram structure for2, both of which have not been observed for the polynuclear cobalt clusters. The magnetic susceptibility investigation showed that complexes1 and2 exhibited ferromagnetic coupling between Co II ions. Further magnetic studies revealed a slight frequency dependence of2, which suggests that2 might be a single‐molecule magnet. Abstract : Two novel mixed‐valent Co13 clusters with unique shieldlike and hexagram core architectures were synthesized and structurally characterized. The magnetic susceptibility investigation showed that they both exhibited ferromagnetic coupling between Co II ions and one of them might be a single‐molecule magnet.